ANALISIS PENGARUH KEMAMPUAN MEMBAYAR KLAIM, PROFITABILITAS, RISIKO UNDERWRITING, DAN REASURANSI TERHADAP SOLVABILITAS PERUSAHAAN ASURANSI (Studi Pada Perusahaan Asuransi Yang Terdaftar di Bursa Efek Indonesia Periode 2008-2013) - Tarigan, Angga Primasandi Kurniawan; Mahfud, M. Kholiq (Faculty of Economics and Business Diponegoro University, 2015)
Solvability takes a big role in an insurance company’s life, they have to make sure that it’s always in a certain minimum condition. Discovering the influennce of Total Claim Paid, Profitability, Underwriting Risk, and Reinsurance to The Solvability of Insurance Companies is the purpose of this research. ROA (Return on Assets) is used as the proxy of profitability and RBC (Risk Based Capital) is used on solvability. Go Public Insurance Companies that listed on BEI are the companies that used as the objects of this research.There are ten insurance companies listed on BEI that can be used as the population of this research, which then processed through purposive sampling to determine the sample by applying some criterias until finally resulted with nine companies as the sample, this research work on the period of 2008-2013, so it will got fifty four data as the observation points. The data that used on this research was secondary data that collected from financial reports of the companies and InfoBank Research Company. The method used in this research was multiple regression analysis, including assumption classic test and used hypothesis test starting F-statistic, T-statistic and then determination of coefficients (R2).The results showed that Total Claim Paid and Underwriting Risk have a positive significant influence on Solvability, ROA doesn’t have significant influence on Solvability, and then Reinsurance has a negative significant influence on Solvability. Berbahasa Inggris.